The Education-Industrial Complex Going Global - Anthony Picciano (Seminar.net)
In 1994, I first wrote about an education-industrial complex that was emerging in the United States. The education-industrial complex was defined as networks of ideological, technophile and for-profit entities that sought to promote their beliefs, ideas, products and services in furtherance of their own goals and objectives. In the years since, the education-industrial complex has grown into a global phenomenon and has become a major force among powerful players (i.e., mega-corporations, international interest groups, and government officials) to influence education policy. This paper describes the present global education-industrial complex and concludes with a call to monitor and study its further evolution.